TOPICAL PROBLEMS OF PREPARATION OF TRADE PERSONNEL AND THE WAY OF THEIR DECISION - Maria A. Nikolaeva; Yuriy N. Kleshchevsky; Olga A. Ryazanova (Высшее образование в России)
In article examines the topical problems facing trade education at the present stage taking into account the requirements stated in Federal state educational standards (for specialized secondary and higher education) and the changes in system after adoption of the Federal Law «About education in the Russian Federation».